2001
DOI: 10.1530/eje.0.1440263
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal responsiveness to parathyroid hormone in pseudohypoparathyroidism

Abstract: Background: Although there have been some case reports suggesting that bone in patients with pseudohypoparathyroidism (PHP) might respond to parathyroid hormone (PTH), no information is available as to whether serum PTH concentration is related to bone metabolic markers or to bone mineral density (BMD) in PHP. Objective: To address these relationships, by comparing intact serum PTH, bone metabolic markers and BMD in patients with PHP with those in patients with idiopathic hypoparathyroidism (IHP) and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 47 publications
3
20
1
Order By: Relevance
“…On the contrary, idiopathic hypoparathyroidism (IHP) cases often have reduced bone turnover and increased BMD, mainly at the trabecular, than the general population . Compared with IHP and non‐surgical hypoparathyroidism patients, PHP subjects, especially pseudohypoparathyroidism type 1b (PHP1B), tend to have lower BMD, indicating incomplete skeletal resistance to PTH may exist . However, when compared with normal controls, patients with PHP1A showed a significantly greater total body BMD .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, idiopathic hypoparathyroidism (IHP) cases often have reduced bone turnover and increased BMD, mainly at the trabecular, than the general population . Compared with IHP and non‐surgical hypoparathyroidism patients, PHP subjects, especially pseudohypoparathyroidism type 1b (PHP1B), tend to have lower BMD, indicating incomplete skeletal resistance to PTH may exist . However, when compared with normal controls, patients with PHP1A showed a significantly greater total body BMD .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, one study reported that PHP1B patients had normal BMDs, whereas the other reported the BMD of the PHP1B patients in their cohort was lower than normal . Notably, both studies found evidence of bone remodeling in PHP1B patients . In addition, no longitudinal data are available from previous serial studies.…”
Section: Introductionmentioning
confidence: 98%
“…Two series studies have been conducted in PHP patients; however, these studies had small sample sizes ( n = 10 and 14) and yielded inconsistent results. Specifically, one study reported that PHP1B patients had normal BMDs, whereas the other reported the BMD of the PHP1B patients in their cohort was lower than normal . Notably, both studies found evidence of bone remodeling in PHP1B patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanatani et al mentioned similar results in March 2001: significantly greater amounts of bone metabolic markers in patients with PHP Ib than, for example, in those with idiopathic hypoparathyroidism and postoperative hypoparathyroidism. The patients with PHP Ib develop skeletal disease because of longstanding secondary hyperparathyroidism (Kanatani et al, 2001;Tollin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%